Peranan Sistem dan Prosedur Penjualan dalam Menunjang Efektifitas Pengendalian Intern Piutan :. Studi Kasus PT. Indomobil Finance Indonesia - Hastoni, Hastoni (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
This research has purposes to study the role of financing system and procedure in supporting internal control of credit. From analysis result, itâs obvious that selling system or procedure supports internal control of credit intensely, besides we come to know that percentage of unsolved credit is influenced by other factors out of agreement system and procedure, among other this things economic condition as a whole. Itâs visible at percentage rising of unsolved credit during 2003. Generally it has been triggered by unstable economic condition so that it has evoked high level dismissal of workers and bankruptcy increase. There for, it is necessary conducting efforts to decrease unsolved credit form period to period including by more strict internal analysis and control to gain qualified lessees or consumers who are able to comply with their responsibilities to the firm. Keywords : Selling System and Procedure; Internal Control